Unveiling the impact of ERAP1 and ERAP2 on migration, angiogenesis and ER stress response - Saulle, Irma; Vitalyos, Alessandra Velia; D’Agate, Daniel; Clerici, Mario; Biasin, Mara (Frontiers in Cell and Developmental Biology, 2025)
Recent studies have investigated the key roles exerted by ERAP1 and ERAP2 in maintaining cellular homeostasis, emphasizing their functions beyond traditional antigen processing and presentation. In particular, genetic variants of these IFNγ-inducible aminopeptidases significantly impact critical cellular pathways, including migration, angiogenesis, and autophagy, which are essential in immune responses and disease processes. ERAP1’s influence on endothelial cell migration and VEGF-driven angiogenesis, along with ERAP2’s role in managing stress-induced autophagy via the UPR, highlights their importance in cellular adaptation to stress and disease outcomes, including autoimmune diseases, cancer progression, and infections. By presenting recent insights into ERAP1 and ERAP2 functions, this review underscores their potential as therapeutic targets in immune regulation and cellular stress-response pathways.